In memory data management and analysis : first and second International Workshops, IMDM 2013, Riva del Garda, Italy, August 26, 2013, IMDM 2014, Hongzhou, China, September 1, 2014, Revised selected papers /: first and second International Workshops, IMDM 2013, Riva del Garda, Italy, August 26, 2013, IMDM 2014, Hongzhou, China, September 1, 2014, Revised selected papers. (2015) - Unknown
No abstract available